دراسة إمكانية إنتاج غذاء مطبوخ من الجبن المنضج ولحم الدجاج - علي علي راضي; صالح فراس احمد; الموسوي ازهار جواد (Al-Nahrain Journal of Science, 2018)
This study aimed to produce a processed ready to eat food from cheese plus boiled chicken meat, by mixing them in different percentage mincing, addition of emulsifying salts and cooking them for 5 min. Different recipes of chicken meat and cheese were tried to achieve acceptable recipe by the consumer. Physical, chemical, microbiological and sensory evaluation properties were carried out for product samples and compared to normal processed cheese, Samples at cooled storage (7±2oc). Results of sensory evaluation declared that characters of color, fat separation, flavor, body, texture and bitterness after one day storage were 9.2 – 10 for processed food product and 10 for control, after 7 days of cold storage at (7±2oC) the decrease were happened in these characters sensory evaluation for product samples compared to indictable after one day storage for normal processed cheese. Total coli form, yeast and mold and Staph. aureus were indictable after one day storage, while after 7 days the total bacterial count were (0.00-25x102) C.F.U./g and 6x102 C.F.U./g for control cheese, and the count for yeast and mold was (0.00-1x102 ) C.F.U./g for processed food product and 1x102 for the control cheese. The percentages of T.S. were 45.49%, fat 14 – 21.5%, protein 17.22 – 24.52% to processed food product compared with 48.38, 21.5, 20.38% respectively in control. Results showed that processed cooked food which was produced from chicken meat plus processed cheese could not gain the target that the product should be relatively better than the processed cheese alone.